Financial Ratio–Based Assessment of Corporate Financial Performance: Evidence from PT Mustika Ratu Tbk (2019–2023) - Yarinidi Angel Zebua; Siswanto Siswanto; Hafni Cholida Nasution (Global Insights in Management and Economic Research, 2026)
Purpose of the study: This study aims to evaluate the financial performance of PT Mustika Ratu Tbk, a publicly listed consumer goods company on the Indonesia Stock Exchange (IDX), over a five-year period from 2019 to 2023. By employing comprehensive financial ratio analysis encompassing liquidity, solvency, and profitability dimensions, the research seeks to provide empirical evidence regarding the company’s financial health and to identify structural strengths and weaknesses in its performance trajectory during a period marked by significant macroeconomic volatility, including the COVID-19 pandemic and subsequent economic recovery. Materials and methods: A descriptive quantitative research design was employed utilizing secondary data derived from audited annual financial statements published on the Indonesia Stock Exchange. Financial performance was assessed through six key ratios: Current Ratio and Quick Ratio (liquidity), Debt-to-Asset Ratio and Debt-to-Equity Ratio (solvency), and Return on Assets and Return on Equity (profitability). Descriptive statistical analysis, including measures of central tendency, variability, and temporal trend analysis, was applied to evaluate performance across the study period. Results were benchmarked against prevailing industry standards established by the Ministry of Industry of the Republic of Indonesia to determine performance adequacy. Results: The findings indicate that PT Mustika Ratu Tbk demonstrated strong liquidity performance, with average Current and Quick Ratios of 252.55% and 159.45% respectively, both exceeding industry benchmarks. Solvency analysis revealed an adequate asset coverage of liabilities (DAR = 29.55%), although capital structure efficiency remained conservative as evidenced by a low Debt-to-Equity Ratio (43.27% against a 90% industry standard). Profitability performance was persistently weak, with average ROA of 2.09% and ROE of 3.24%, both substantially below the 30% industry expectation, although a recovery trend was observable from 2021 onward. Conclusions: While the company exhibits a sound short-term financial position and manageable debt levels, its persistent inability to generate adequate returns from assets and equity suggests structural inefficiencies in operational and strategic management. These results underscore the critical need for profitability-oriented reforms, including operational cost optimization, strategic asset redeployment, and revenue diversification, to enhance long-term financial sustainability and shareholder value creation.